Historical Critics of Sibt Ibn Al-Jawzy B.654 AH /1256 AD in the Book " The Mirror of Time in the Chronicles of Nobles" - شمخي يابر عويد العطافي, د.; فايز خلف عمير الخويلدي , م.م. (lark, 2021)
Sibt Ibn Al-Jawzi is considered as one of the men of the intellectual movement in the seventh century AH. He was distinguished by the production of many books in the various fields of knowledge, including historical ones, the most famous  is "The Mirror of Time in the Chronicles of Notables", which considered as an important historical encyclopedia in which he transmitted a lot of news about the history of nations and the previous ages, and then he is distinguished in writing history by being a skilled critic historian in transmission, so he doubted, weighed, gave reasons and corrected many narrations, rejecting some narrations that are not accepted by the logic of mind and reality, and put forward some good opinions and additions,  accordingly his book became an important rich resource that from which many research historians extracted their historical information .